Occurrence of natural parasitism in Euschistus heros (Heteroptera: Pentatomidae) eggs by Telenomus sp. aff. podisi in soybean in Amambay, Paraguay - Ferreira-Agüero, Marcos Arturo; Álvarez R., Nathalia Carolina; Coelho, João Batista (Revista Colombiana de Entomología, 2023)
Euschistus heros (Hemiptera: Pentatomidae) is the main pest of soybean in Amambay, Paraguay; the intense damage to the pods results in decreased production and economic losses for farmers. Parasitoids that naturally control their populations are important agents to include in integrated pest management. In this investigation, the occurrence of natural parasitism of E. heros eggs by Telenomus sp. aff. podisi (Hymenoptera: Scelionidae) in soybean was determined. The parameters evaluated were: The number of parasitized eggs, parasitism index, and percentage of emerged parasitoids. Photographic images of the parasitoids were also produced to describe their main morphological characteristics. The research was carried out in six districts of the department of Amambay, Paraguay. E. heros eggs were randomly collected from 50 soybean plants, transferred to the laboratory, and conditioned in a climate chamber. After the emergence of the parasitoids, they were placed in a freezer to produce death and in 70 % alcohol for preservation. For the identification of specimens, the parasitoid samples were sent to the laboratory of the Biological Institute of Campinas, Sao Paulo, Brazil. Additionally, photographic images of the recovered adult parasitoids were prepared to describe their main morphological characteristics. Only the parasitoid T. sp. aff. podisi was identified. The number of parasitized eggs was 683, the parasitism index was 92.67 %, and the percentage of emerged parasitoids, was 22.55 %. This is the first report of the natural occurrence of T. sp. aff. Podisi in E. heros eggs in Paraguayan soybean crops, an important biological pest control agent.